2010
DOI: 10.1021/ja907581s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Long-Range Diffusion in Phospholipid Membranes Studied by Quasielastic Neutron Scattering

Abstract: The motion of phospholipids has previously been studied on many time scales due to the significance for living cells and technological applications. The motions on a pico- to nanosecond time scale were determined by quasielastic neutron scattering (QENS) to be much faster than the ones on the microsecond scale covered by fluorescence recovery after photobleaching (FRAP). This was explained by assuming that the molecules rattle fast in a cage of neighbors (observed with QENS) from which they escape once in a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
186
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(206 citation statements)
references
References 29 publications
(42 reference statements)
20
186
0
Order By: Relevance
“…60 As can be seen in the inset of Fig. 4, the H free model is preferred to the H 2/3 model because the χ 2 PDF has its peak at a smaller value, therefore disfavoring the E g = E t scenario.…”
Section: The Intramolecular Structure Of F-112mentioning
confidence: 96%
See 1 more Smart Citation
“…60 As can be seen in the inset of Fig. 4, the H free model is preferred to the H 2/3 model because the χ 2 PDF has its peak at a smaller value, therefore disfavoring the E g = E t scenario.…”
Section: The Intramolecular Structure Of F-112mentioning
confidence: 96%
“…Parameter The proposed algorithm to find the structure describing the data within their errors is implemented in the free and open, publicly available program FABADA, 59 and it has already successfully been used to describe the dynamics from quasielastic neutron-scattering experiments 60,61 and from dielectric spectroscopy. 62 …”
Section: B Fit Functionmentioning
confidence: 99%
“…And ballistic lipid motion in fluid membranes has indeed been recently reported from quasielastic neutron scattering (QENS) using a neutron backscattering spectrometer [8]. Furthermore, it has been reported that lipids move coherently in loosely bound clusters, rather than as independent molecules [9][10][11]. A "hopping" diffusion of lipids into nearest neighbour sites was observed in single supported bilayers [12], and, recently, it has also been suggested that there is a flow-like component to the motion of the lipid molecules over long length scales [11].…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, it has been reported that lipids move coherently in loosely bound clusters, rather than as independent molecules [9][10][11]. A "hopping" diffusion of lipids into nearest neighbour sites was observed in single supported bilayers [12], and, recently, it has also been suggested that there is a flow-like component to the motion of the lipid molecules over long length scales [11]. In biology, diffusion often occurs in crowded media, which was found to lead to anomalous diffusion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of multilamellar liposomal membranes by neutron scattering (Busch et al, 2010) and simulation (Falck et al, 2008) have found evidence for flow-like behavior, in which lipid molecules move collectively.…”
Section: Measurements Of D L In Model Systemsmentioning
confidence: 99%